Incontinence and constipation in adolescent patients with anorexia nervosa—Results of a multicenter study from a German web‐based registry for children and adolescents with anorexia nervosa. Issue 2 (16th October 2019) - Mattheus, Hannah K.; Wagner, Catharina; Becker, Katja; Bühren, Katharina; Correll, Christoph U.; Egberts, Karin M.; Ehrlich, Stefan; Fleischhaker, Christian; Föcker, Manuel; Hahn, Freia; Hebebrand, Johannes; Herpertz‐Dahlmann, Beate; et al.
Abstract: Objective: Nocturnal enuresis (NE), daytime urinary incontinence (DUI), and fecal incontinence (FI) are common disorders in childhood and are frequently accompanied by comorbid psychiatric disorders. Despite a high association between urinary and fecal incontinence with psychiatric and neurodevelopmental disorders, research on comorbidity between incontinence and anorexia nervosa (AN) remains scarce. Yet, it is well known that somatic consequences of AN include metabolic and gastrointestinal disorders. The study sought to assess the prevalence of incontinence and constipation in children and adolescents with AN and to examine associations of these two symptoms with body weight at admission and with BMI changes during inpatient treatment. Methods: Data collected between 2015 and 2017 by a multicenter German web‐based registry for AN were analyzed. Three hundred and forty‐eight patients with AN (96.3% female, mean age = 15.1 ± 1.8 years) were assessed regarding AN subtype, psychiatric comorbidity, body weight, incontinence, and constipation. Results: Overall, 27.6% of patients had constipation, 1.8% had NE and 1.8% DUI. Prevalence of constipation did not significantly differ between AN subtypes. Constipation did not lead to any significant differences in weight/BMI changes during inpatient treatment. Discussion: This is the largest study of incontinence and constipation in patients with AN, so far. Our results indicate that constipation is highly prevalent in adolescent patients with AN and reflects a clinically relevant condition. Despite, patients with AN do not have an increased prevalence of incontinence compared with the general population. Future studies should include medical examinations like ultrasound and physical examination of the lower abdomen to evaluate the severity of constipation.